2020
DOI: 10.1002/ejic.202000750
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Schiff Base‐Substituted Diselenides and ‐tellurides with Ni(II), Pd(II) and Pt(II) Phosphine Complexes

Abstract: The salicylidene Schiff bases of bis(2-aminophenyl)diselenide and-ditelluride react with [M II Cl 2 (PPh 3) 2 ] (M = Ni, Pt) or [Pd II (OAc) 2 (PPh 3) 2 ] with formation of square-planar complexes with the general formulae [M II (L Y)(PPh 3)] (M = Ni, Pd, Pt, Y = Se, Te). The ligands coordinate to the metals as tridentate {O,N,Se/Te} chelates. The reduction of the dichalcogenides and the formation of the chalcogenolato ligands occurs in situ by released PPh 3 ligands. A mechanism for such reactions has been [a

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 91 publications
(152 reference statements)
1
14
0
Order By: Relevance
“…As a result, the protons of the phenyl rings attached to the selenium and tellurium atoms are more deshielded than those of the phenolate ring. This is most likely caused by the presence of a stronger π and/or σ donor in the trans position to the imine compared to the phosphine in the corresponding [Pd­(L′ Y )­(PPh 3 )] complexes . Therefore, a considerable degree of back-donation into the π* orbital of the Schiff bases or less σ donation of the Schiff base nitrogen atoms can be assumed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the protons of the phenyl rings attached to the selenium and tellurium atoms are more deshielded than those of the phenolate ring. This is most likely caused by the presence of a stronger π and/or σ donor in the trans position to the imine compared to the phosphine in the corresponding [Pd­(L′ Y )­(PPh 3 )] complexes . Therefore, a considerable degree of back-donation into the π* orbital of the Schiff bases or less σ donation of the Schiff base nitrogen atoms can be assumed.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we developed a reliable method for the preparation of defined monomeric organochalcogenolato complexes from dichalcogenides via a reduction by intrinsically released phosphine ligands of nickel, palladium, platinum and rhenium starting materials. …”
Section: Introductionmentioning
confidence: 99%
“…1,9 Therefore, the formation of several tellurium compounds can result from the Te–Te or Te–C bond cleavage. 10–14…”
Section: Introductionmentioning
confidence: 99%
“…1,9 Therefore, the formation of several tellurium compounds can result from the Te-Te or Te-C bond cleavage. [10][11][12][13][14] Recently, our research group reported the synthesis and structural characterization of exotic pyridyltellurolate clusters, zwitterionic and coordination compounds using bis(2-pyridyl) ditellane (Fig. 1) as a precursor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation